Hints for the busy housewife (London : Health & Cleanliness Council)
1939-05 1939 1930s 50 pages : illustrations HINTS FOR THE BUSY HOUSEWIFE After his gown has been removed, his face is washed, starting gently with the eyelids, and being careful not to touch the delicate mucous membrane of the eyes. Pieces of clean, boiled rag, or preferably swabs of cotton-wool from the bowl of cool boiled water, should be used for this purpose, each swab being discarded after use. The nostrils may be gently cleaned with tiny rolls of wool. The inside of the mouth should not be touched as long as it is healthy, for it has been found that vigorous cleansing of the mouth may damage the lining of it and lead to infection. [photograph] If you have not got a thermometer, take the temperature this way. (Photograph taken at the Nursery Training School Wellgarth Road, London, N.W.11.) Baby is then entirely undressed and wrapped in the warm towel, all except his head. The scalp is gently but firmly rubbed with a good lather of soap on the hands, held over the bath to have the soap thoroughly rinsed off, and dried with a soft towel. The temperature of the bath should again be tested with the thermometer — or if no thermometer is Page Forty-three 177/5/8/1